Everybody is a liar eaudiobook - Constantine, Liv (Books on Tape, 2024)
The New York Times bestselling author of The Next Mrs. Parrish delivers another spellbinding story of betrayal and deceit in this audiobook original, Everybody Is a Liar . When Julie Buckley, a successful mystery writer, suspects her husband of cheating, she turns to her best friend, Darby, for advice. When Darby suggests couples therapy, Julie and Oliver find themselves discussing Oliver’s betrayal with their new therapist, Liza. Liza is competent and reassuring, and her advice and Oliver’s openness to change seem to be helping the couple rebuild their relationship.   But when murder strikes in this small Connecticut town, Liza begins to worry there is a connection between Oliver and another one of her patients and the confidences they have shared with her become the key to solving the murder. As Liza digs deeper, she comes to believe that everybody is a liar.